Hubungan Asupan Zat Gizi Makro dan Aktivitas Fisik dengan Status Gizi Mahasiswa Ilmu Gizi UMS - Idek Zahra; Dyah Intan Puspitasari; Elida Soviana (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia is currently facing a triple burden of nutritional problems, including stunting, wasting, and obesity, as well as micronutrient deficiencies such as anemia. These issues are particularly prevalent among adolescents and adults, with common problems including undernutrition, overnutrition, and iron deficiency leading to anemia.This study was conducted in the Nutrition Study Program, Faculty of Health Sciences, Universitas Muhammadiyah Surakarta. It aimed to examine the relationship between macronutrient intake (carbohydrates, fats, and proteins), physical activity, and the nutritional status of students. A cross-sectional study design was employed to collect data at a single point in time and analyze the associations between variables. The results showed that there was no significant relationship between carbohydrate intake and nutritional status, as indicated by a p-value of 0.217 and a correlation coefficient (r) of 0.135. Therefore, the null hypothesis (H0) was accepted. However, a significant relationship was found between fat intake and nutritional status, with a p-value of 0.049, suggesting that fat consumption plays a role in determining the nutritional status of students. On the other hand, protein intake did not show a significant relationship with nutritional status, as indicated by a p-value of 0.470. Similarly, physical activity was not significantly associated with nutritional status, with a p-value of 0.228. In conclusion, the study found that among the variables examined, only fat intake had a significant effect on students' nutritional status. Carbohydrate intake, protein intake, and physical activity did not demonstrate meaningful associations. These findings can serve as a basis for evaluating and improving dietary patterns and healthy lifestyle habits among university students.